Photoprotective properties, chemical, biological and product formulation studies on Zanthoxylum rhetsa (Roxb.) DC - Santhanam, Rameshkumar (2016)
Protection against photo oxidative damages is essential for living organisms. Humans especially need to counteract oxidative stress and damages caused by harmful UV radiations. Zanthoxylum rhetsa (Indian Prickly Ash) is an aromatic tree, commonly found in tropical regions. Various parts of this plant species have been used medicinally to treat health disorders such as diabetes, cholera, microbial infections and rheumatism. Recently, the seeds of Z. rhetsa, has been investigated for its sunscreen potential with promising results. However the photo protective properties of other parts of this plant species remains unexplored. The objective of this study is to evaluate the bark material of Z. rhetsa for its photo protective and anti-aging properties. The crude methanolic extract of Z. rhetsa bark and its various solvent fractions were preliminarily screened, in vitro, for their UV protection properties. In comparison with other fractions, the ethyl acetate fraction revealed the highest SPF value (13.36 at 100 μg/ml), significant UVA/UVB absorption, free radical scavenging, anti-collagenase and anti-elastase properties. Subsequently, the extract and fractions were tested for their cytotoxic effect against human dermal fibroblasts (HDF) and mouse melanoma (B16-F10), representing normal and cancer cell lines, respectively. All the test samples were found to be nontoxic to HDF cells. However, the chloroform fraction revealed cytotoxicity towards the melanoma B16-F10 cells with an IC50 value of 132.7 μg/ml. Diverse array of compounds present in the solvent fractions were identified using GC-MS analysis. Compounds such as lupeol, yangambin, kobusin, columbamine and hesperidin were isolated and identified from the bioactive fractions of Z. rhetsa. All the isolated compounds were tested for their cytotoxic effect against HDF and melanoma B16- F10 cell lines. The compounds were all found to be non-toxic to HDF cells. Meanwhile, two of the isolated compounds, kobusin and columbamine, were observed to have significant cytotoxic effect against the melanoma B16-F10 cells, with IC50 value of 112.2 μg/ml and 195.6 μg/ml, respectively. Furthermore the isolated compounds were tested for their SPF value, where hesperidin showed an SPF value of 13.38 at 100 μg/ml, which is almost the same as the SPF value of the ethyl acetate fraction. This indicated that the UV protection property of the solvent fraction is largely due to the presence of hesperidin. The ethyl acetate fraction and hesperidin were further tested for UVB induced cytotoxicity, and for inhibition of inflammatory cytokines (IL-1β, IL-6 and TNF-α) and of MMPs (collagenase; MMP1, stromelysin-1; MMP3 and gelatinase; MMP9). The ethyl acetate fraction and hesperidin significantly prevent cell death, inhibited the expressions of pro-inflammatory cytokines and MMPs. Due to the favourable UV protection properties of the ethyl acetate fraction, it was further evaluated for its suitability as an active ingredient (10% w/w) in two sunscreen formulations (F1 & F2). The F1 and F2 cream, respectively showed an SPF value of 3.60 ± 0.28 and 6.90 ± 0.57, a UVA/UVB ratio of 0.469 and 0.538 and critical wavelength of 365.3 and 360, with moderate boot star rating, pseudo plastic behaviour and high microbial growth resistance. Altogether, these results support the photo protective property of the Z. rhetsa bark and its extract, particularly the ethyl acetate fraction of the methanolic extract has the potential to be developed further as an active ingredient in sunscreen and other cosmeceutical products. To the best of our knowledge this is the first report on the photo protective properties of the bark material of Z. rhetsa in extract as well as in cream formulation.